Differences in Arginine Requirement for Growth Among Arginine-Utilizing Mycoplasma Species - Hahn, Ricardo G. (1974)
The essentiality of arginine for initiation of growth of arginine-utilizing, nonglycolytic Mycoplasma species from small populations was studied by growing the organisms in a semisynthetic medium proven to be free from arginine by chemical and biological assays. Initiation of growth of two strains of M. arginini did not require arginine, whereas another strain of M. arginini required 4 mM arginine, as did M. gallinarum. M. hominis grew in 0.4 mM arginine. A species which utilizes both arginine and glucose, N. fermentans, did not require arginine but did require glucose for growth. When mycoplasmata were grown in human heteroploid cell cultures employing medium free from arginine but supplemented with citrulline, similar results were obtained: two M. arginini strains grew in the absence of arginine, whereas growth of M. gallinarum and M. hominis and a third M. arginini strain was dependent on arginine even though mammalian cells were present. The arginine deiminases were heterogeneous serologically: antisera to M. hominis and M. arginini showed reciprocal inhibition of their enzymes but did not inhibit arginine deiminase from M. gallinarum. Antiserum to M. gallinarum inhibited only M. gallinarum enzyme.